1998
DOI: 10.1002/hep.510280407
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of the oral administration of midodrine, an ?-adrenergic agonist, on renal hemodynamics and renal function in cirrhotic patients with ascites

Abstract: The effects of the acute administration of arterial vasoconstrictors on renal plasma flow (RPF) and urinary sodium excretion (UNaV) in cirrhotic patients with ascites with or without hepatorenal syndrome (HRS) are still controversial. As a consequence, vasoconstrictors are not actually used in the treatment of renal sodium retention or HRS in these patients, regardless of the several lines of evidence suggesting that these renal functional abnormalities are related to a marked arterial vasodilation. The lack o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
1
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(108 citation statements)
references
References 34 publications
6
100
1
1
Order By: Relevance
“…In another study on acute effects of midodrine, an improvement in GFR and U Na was observed in patients with ascites, and no effect was seen in patients with type 2 HRS. 25 Although the V1 receptor agonists induce splanchnic vasoconstriction, the effects of alpha-1-adrenergic agonists on splanchnic vasodilatation, which is considered a key factor in the pathogenesis of ascites, 5 are unknown in patients with cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…In another study on acute effects of midodrine, an improvement in GFR and U Na was observed in patients with ascites, and no effect was seen in patients with type 2 HRS. 25 Although the V1 receptor agonists induce splanchnic vasoconstriction, the effects of alpha-1-adrenergic agonists on splanchnic vasodilatation, which is considered a key factor in the pathogenesis of ascites, 5 are unknown in patients with cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the administration of agents that decrease bile acid levels, bacterial translocation, or secondary consequences of endotoxin circulation and inflammation could be considered therapeutic options. 2,108,138,[161][162][163][164][165][166][167][168][169] For instance, ursediol (ursodeoxycholic acid) has been shown in some studies to decrease bile acid toxicity and endotoxin levels, as well as soluble ICAM-1 and TNF-␣ levels, and even decrease intestinal production of nitric oxide. 146,152,[170][171][172][173][174][175] In addition, MARS treatments (albumin dialysis with hemofiltration) have been shown to decrease TNF-␣ and IL-6 levels and improve survival in type 1 HRS.…”
Section: Treatment Of Hrsmentioning
confidence: 99%
“…Similarly, Krag and colleagues found that patients with a low cardiac index (< 1.5L/ min/m 2 ) significantly developed more hepatorenal syndrome and had decreased survival rate compared to those with a cardiac index above 1.5 L/min/m 2 [33] . Correspondingly, several studies confirmed this concept by showing that midodrine, an alpha-1 adrenergic agonist, was beneficial in patients with advanced cirrhosis [35][36][37][38][39] . Midodrine therapy increased urinary volume, urinary sodium excretion, blood pressure, and decreased plasma renin activity and overall mortality [39] .…”
Section: Blood Pressure and Cirrhosismentioning
confidence: 98%